Bahan Ajar Berbasis TIK pada Diklat Teknis Fungsional Peningkatan Kompetensi Pengawas Madrasah/PAI di Balai Diklat Kegamaan Makassar - Ma'arif; Ratna Prilianti (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2021)
[TEACHING MATERIALS BASED ON ICT ON THE FUNCTIONAL TECHNICAL TRAINING OF THE COMPETENCEIMPROVEMENT OF MADRASAH/ISLAMIC EDUCATION SUPERVISORS AT RELIGIOUS TRAINING CENTER OFMAKASSAR]. The researchs’ aim is to evaluate teaching materials based on ICT on the Functional Technical Training of the Competence Improvement of Madrasah/Islamic Education supervisors at Religious Training Center of Makassar. This evaluation includes aspects of the substance of the material, design of the learning,appearance/visual communication, and the use of the software. This research is qualitative research with a case study form. The data collecting through interviews, observation, and documentation. While the data analysis uses qualitative data analysis by data reduction, data presentation, conclusion drawing, and verification. The results showed that even though some of these aspects still needed improvement, in general, the quality of teaching materials used by trainers at the Religious Training Center of Makassar was good enough. Trainers’ understanding of the aspects that must be considered in making teaching materials based on ICT must be continuously improved in the form of real implementation, namely good teaching materials based on ICT. For that reason, mastery of ICT is an absolute for the trainers and there must be strong management support in encouraging trainers to compile and develop teaching materials that can support the achievement of the training objectives.